Analisis Penerapan Model Pembelajaran Predict Observe Explain terhadap Pemahaman Konsep Sains Siswa di Sekolah Dasar - noviani ulfa; Ramdhan Witarsa; Wida Rianti (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2021)
This study aims to describe the application of the predict observe explain learning model to students' understanding of science concepts in elementary schools. The research method used is descriptive research method with meta-analysis technique, with steps of data collection, data reduction, data display, discussion, and drawing conclusions. The results showed that of the 32 articles discussing the application of the predict observe explain learning model and the understanding of students' science concepts in elementary schools published in accredited journals in the last 10 years, only 4 articles were found that discussed both (the application of the predict observe explain learning model to understanding the concept science students in elementary school). The conclusion of this study is that the application of the predict observe explain learning model to students' understanding of science concepts in elementary schools is very rarely done. The steps of the predict observe explain learning model that are applied are different from one another. Likewise, the aspects of understanding the concepts studied differ from one another. Continuous assistance is needed for elementary school teachers to be able to implement the steps of the predict observe explain and explain learning model and aspects of understanding concepts that are in accordance with the original theory